Species composition, relative abundance and distribution of social wasps fauna on different ecosystems - Souza, M. M.; Brunismann, A. G.; Clemente, M. A. [UNESP] (Univ Estadual Feira Santana, 2017)
The state of Minas Gerais has high biodiversity, characterized by strong ecosystem heterogeneity that favors high richness of social wasps. There are currently 109 species known to occur in the state, however, there is lack of information concerning the distribution of these social insects among different ecosystems. The objective of this study was to evaluate social wasp species richness and distributions by ecosystem, thereby generating data for use in discerning relevant and priority environments for vespid conservation in Minas Gerais. We evaluated articles, theses, and dissertations published up to the year 2016 containing data on biodiversity of social wasps in natural and agricultural environments. We found 18 studies, in which the highest reported species richness was in semideciduous seasonal forest (n = 68), followed by Cerrado (n = 53), ombrophilous forest (n = 39), deciduous seasonal forest, and campos rupestres (n = 35). The lowest richness was reported in mixed forest (n = 21) and high-altitude fields (n = 19). Considering the high degree of landscape diversity of the state of Minas Gerais, more studies are needed to accurately assess social wasp diversity in these ecosystems, especially Cerrado. Ombrophilous and deciduous forests should be considered strongly relevant for these social insects, especially the Rio Doce State Park and the Rio Pandeiros Wildlife Refuge.
Keywords: Polistinae; Biodiversity; Species inventories